(untitled) (Foro de Educacion, 2022)
The aim of this article is to analyse how neoliberal principles in education create a state of precariousness. The question that will guide the problematisation and the argumentation of the work is: What is the «status» of precariousness in the current order and how does it manifest itself - expressly or inadvertently - in the contemporary educational field? In order to address this question, a theoretical-analytical exercise has been carried out based on a review of relevant literature on the relationship between neoliberalisation and education. As a central hypothesis, we propose that the processes of precarisation constitute an objective necessity for the expansion and reproduction of the new neoliberal order. In addition, this order requires the production of a specific type of subjectivity that normalizes «precariousness» as a new historical condition, producing a particular notion of subjectivity and agency. The intersection between objective needs and the production of a particular subjectivity is produced in the cultural space through «pedagogies of precariousness». The installation of such pedagogies in formal education systems will be verified through the analysis of three predominant figures: the entrepreneur, the apprentice of competences and the teacher as technician. Finally, it is analysed how a «pedagogy of possibilities» could be opposed to «pedagogies of precariousness», enabling other forms of educational relations and new political-pedagogical horizons.